Chronic Treatment with Ivabradine Does Not Affect Cardiovascular Autonomic Control in Rats - Silva, Fernanda C.; Paiva, Franciny A.; Müller-Ribeiro, Flávia C.; Caldeira, Henrique M. A.; Fontes, Marco A. P.; de Menezes, Rodrigo C. A.; Casali, Karina R.; Fortes, Gláucia H.; Tobaldini, Eleonora; Solbiati, Monica; Montano, Nicola; Dias Da Silva, Valdo J.; et al. (Frontiers in Physiology, 2016)
A low resting heart rate (HR) would be of great benefit in cardiovascular diseases. Ivabradine – a novel selective inhibitor of hyperpolarization-activated cyclic nucleotide gated (HCN) channels– has emerged as a promising HR lowering drug. Its effects on the autonomic HR control are little known. This study assessed the effects of chronic treatment with ivabradine on the modulatory, reflex and tonic cardiovascular autonomic control and on the renal sympathetic nerve activity (RSNA). Male Wistar rats were divided in 2 groups, receiving intraperitoneal injections of vehicle (VEH) or ivabradine (IVA) during 7 or 8 consecutive days. Rats were submitted to vessels cannulation to perform arterial blood pressure (AP) and HR recordings in freely moving rats. Time series of resting pulse interval and systolic AP were used to measure cardiovascular variability parameters. We also assessed the baroreflex, chemoreflex and the Bezold-Jarish reflex sensitivities. To better evaluate the effects of ivabradine on the autonomic control of the heart, we performed sympathetic and vagal autonomic blockade. As expected, ivabradine-treated rats showed a lower resting (VEH: 362 ± 16 bpm vs. IVA: 260 ± 14 bpm, p=0.0005) and intrinsic HR (VEH: 369 ± 9 bpm vs. IVA: 326 ± 11bpm, p=0.0146). However, the chronic treatment with ivabradine did not change normalized HR spectral parameters LF (nu) (VEH: 24.2 ± 4.6 vs. IVA: 29.8 ± 6.4; p>0.05); HF (nu) (VEH: 75.1 ± 3.7 vs. IVA: 69.2 ± 5.8; p>0.05), any cardiovascular reflexes, neither the tonic autonomic control of the HR (sympathovagal index; VEH: 0.91± 0.02 vs. IVA: 0.88 ± 0.03, p=0.3494). We performed the AP, HR and RSNA recordings in urethane-anesthetized rats. The chronic treatment with ivabradine reduced the resting HR (VEH: 364 ± 12 bpm vs. IVA: 207 ± 11 bpm, p<0.0001), without affecting RSNA (VEH: 117 ± 16 vs. IVA: 120 ± 9 spikes/sec, p=0.9100) and mean arterial pressure (VEH: 70 ± 4 vs. IVA: 77 ± 6 mmHg, p=0.3293). Our results suggest that, in health rats, the long-term treatment with ivabradine directly reduces the HR without changing the RSNA modulation and the reflex and tonic autonomic control of the heart.